CXCL8 and the peritoneal metastasis of ovarian and gastric cancer - Xuanrong Fu; Qimeng Wang; Hang Du; Huifang Hao (Frontiers in Immunology, 2023)
CXCL8 is the most representative chemokine produced autocrine or paracrine by tumor cells, endothelial cells and lymphocytes. It can play a key role in normal tissues and tumors by activating PI3K-Akt, PLC, JAK-STAT, and other signaling pathways after combining with CXCR1/2. The incidence of peritoneal metastasis in ovarian and gastric cancer is extremely high. The structure of the peritoneum and various peritoneal-related cells supports the peritoneal metastasis of cancers, which readily produces a poor prognosis, low 5-year survival rate, and the death of patients. Studies show that CXCL8 is excessively secreted in a variety of cancers. Thus, this paper will further elaborate on the mechanism of CXCL8 and the peritoneal metastasis of ovarian and gastric cancer to provide a theoretical basis for the proposal of new methods for the prevention, diagnosis, and treatment of cancer peritoneal metastasis.